Risk of Parkinson’s Disease (PD) in patients with diabetes using thiazolidinedione (TZD): A systematic review, meta-analysis, and meta-regression - Kezia Christy Gunawan; Timotius Ivan Hariyanto (Romanian Journal of Neurology, 2023)
Background. T Parkinson’s Disease (PD) stands as the neurodegenerative disorder with the second highest incidence, leading to substantial disability and death rates. Research to date suggests a potential increased risk for PD development in individuals with diabetes, yet the correlation between PD and the use of antidiabetic drugs remains to be fully understood. This study aims to investigate the relationship between thiazolidinedione (TZD) use with the risk of PD in patients with diabetes. Methods. A search of literature was carried out using certain keywords across four databases up until December 11th, 2022: Europe PMC, Scopus, Medline, and Cochrane Library. The review included all studies assessing the risk of Parkinson’s Disease (PD) in patients with diabetes who were treated with thiazolidinediones (TZDs). The pooled risk ratios (RRs) with 95% confidence intervals (CIs) were determined using random-effects models. Results. Our meta-analysis from 12 observational studies revealed that TZD use was associated with reduced risk of PD in patients with diabetes (RR 0.75; 95%CI: 0.63 – 0.91, p=0.003, I2 = 92%). The neuroprotective impact of thiazolidinediones (TZDs) against Parkinson’s Disease (PD) did not show significant variation based on patient characteristics like age (p=0.3380), gender (p=0.9761), hypertension (p=0.1849), smokers (p=0.1476), stroke (p=0.4810), head injury (p=0.5025), and diabetes duration (p=0.2533). Conclusions. This study suggests that the use of TZD in patients with diabetes has a positive neuroprotective effect on the risk of PD. However, to validate these results, further randomized clinical trials (RCTs) are necessary.